KARAKTERISTIK HABITAT Syzygium pycnanthum (Merr.) L.M. Perry DI GUNUNG BAUNG, JAWA TIMUR - Deden Mudiana (Pusat Penelitian dan Pengembangan Hutan, 2017)
ABSTRACTMount Baung is one of the conservation areas having lowland monsoon forest ecosystem in East Java. Diversity of plant species along with its environmental conditions creates such a unique ecosystem. One of plant species commonly found in Mount Baung is Syzygium pycnanthum (Merr.) L.M. Perry. This species belongs to Myrtaceae family. Research on habitat ecology of the species was conducted to determine distribution, population structure and character of its growing site at Mount Baung. The methods including exploration, mapping and sampling plots of observation with a total area of 10 ha were conducted to obtain data on the distribution and growing site character of the species. A total of 235 individuals were recorded in the observation plots, consisting of 42 seedlings, 75 saplings, 49 poles and 69 trees. In general, S. pycnanthum develops a normal population structure to be able to grow, as shown by the growth curve that perform a reverse J-shaped. Habitat of S. pycnanthum at Mount Baung is located in the slope areas ranged from sloping to steep condition. In the regeneration phase (seedlings and saplings), S. pycnanthum grows widely in a shaded slope area and close to bamboo clumps (Bambusa blumeana). Meanwhile the poles and trees of the species grow well in a more open space along with mixed vegetation of shrubs, trees and a few bamboos. Number of individual trees and altitude are environmental factors affecting the existence of S. pycnanthum in Mount Baung.Key words: Habitat, Syzygium pycnanthum, Mount Baung, vegetation.ABSTRAKGunung Baung adalah salah satu kawasan konservasi yang memiliki tipe ekosistem hutan munson dataran rendah di Jawa Timur. Keanekaragaman spesies tumbuhan beserta kondisi lingkungan yang terdapat di dalamnya membentuk suatu ekosistem yang khas. Salah satu spesies tumbuhan yang cukup banyak dijumpai di Gunung Baung adalah Syzygium pycnanthum (Merr.) L.M. Perry. Spesies ini termasuk ke dalam suku Myrtaceae (jambu-jambuan). Penelitian ekologi habitat spesies ini dilakukan untuk dapat mengetahui persebaran, struktur populasi serta karakter tempat tumbuhnya di Gunung Baung. Metode eksplorasi, pemetaan dan pembuatan petak-petak sampling pengamatan dengan total luas 10 ha dilakukan untuk mendapatkan data persebaran dan karakter tempat tumbuh spesies ini. Sebanyak 235 individu tercatat dalam petak pengamatan, terdiri atas 42 individu tingkat semai, 75 individu tingkat pancang, 49 individu tingkat tiang dan 69 idividu tingkat pohon. Secara umum jenis ini memiliki struktur populasi yang normal untuk mampu berkembang, dimana kurva strata pertumbuhannya berbentuk “J terbalik”. Tempat tumbuh S. pycnanthum di Gunung Baung adalah di daerah lereng mulai landai hingga curam. Pada fase permudaan (strata semai dan pancang) jenis ini banyak tumbuh di daerah lereng pada tempat yang ternaungi dan berdekatan dengan rumpun bambu duri (Bambusa blumeana). Pada strata tiang dan pohon jenis ini banyak tumbuh di tempat yang lebih terbuka dengan vegetasi campuran semak, pohon dan sedikit bambu. Faktor jumlah individu pohon dan ketinggian tempat adalah faktor lingkungan yang mempengaruhi keberadaannya di Gunung Baung.Kata kunci: Habitat, Syzygium pycnanthum, Gunung Baung, vegetasi.